The state-dependent impact of changes in bank capital requirements - Jan Hannes Lang; Dominik Menno (European Central Bank (ECB), 2023)
Based on a non-linear equilibrium model of the banking sector with an occasionally-binding equity issuance constraint, we show that the economic impact of changes in bank capital requirements depends on the state of the macro-financial environment. In "normal" states where banks do not face problems to retain enough profits to satisfy higher capital requirements, the impact on bank loan supply works through a "pricing channel" which is small: around 0.1% less loans for a 1pp increase in capital requirements. In "bad" states where banks are not able to come up with sufficient equity to satisfy capital requirements, the impact on loan supply works through a "quantity channel", which acts like a financial accelerator and can be very large: up to 10% more loans for a capital requirement release of 1pp. Compared to existing DSGE models with a banking sector, which usually feature a constant lending response of around 1%, our state-dependent impact is an order of magnitude lower in "normal" states and an order of magnitude higher in "bad" states. Our results provide a theoretical justification for building up a positive countercyclical capital buffer in "normal" macro-financial environments.
Keywords: D21; E44; E51; G21; G28; 330; Bank capital requirements; loan supply; dynamic stochastic equilibrium model; financial accelerator; global solution methods